PENINGKATAN LITERASI KESEHATAN MENTAL MASYARAKAT MELALUI EDUKASI PSIKOLOGIS BERBASIS KOMUNITAS - Monika Nina Ginting; Sulastri Br Ginting (INSTITUT KESEHATAN DELI HUSADA, 2026)
Mental health is an integral component of overall health that affects individuals’ social, emotional, and productive functioning. However, mental health literacy in the community remains relatively low, as indicated by limited understanding of mental health concepts, early signs of psychological problems, strategies for maintaining mental well-being, and the importance of seeking appropriate help. This condition may reinforce stigma and hinder promotive and preventive efforts in the community. This community service program aimed to improve mental health literacy through community-based psychological education. The program was implemented using an educational and participatory approach consisting of four stages: preparation, implementation, evaluation, and follow-up. The activities included health education sessions, interactive discussions, simple simulations, and community assistance. The evaluation was conducted using pre-tests and post-tests, observation of participants’ involvement, and participant feedback. The expected outcomes included improved public knowledge of mental health, increased ability to identify early signs of psychological problems, reduced stigma, and greater awareness of maintaining mental well-being and accessing appropriate support services. The indicators of success were reflected in the implementation of activities as planned, active participant engagement, and improved participants’ understanding after attending the program.